UTILIZING EDUCATIONAL TECHNOLOGY IN EMPOWERING SPECIAL EDUCATION: EXPERIENCES AND CHALLENGES OF STUDENTS AND TEACHERS - Supermaniam, Murugesu; Hamdan, Norfatin Faizah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the integration of educational technology within Malaysia’s special education context, focusing on the lived experiences of 47 preservice teachers during their practicum placements. Educational technology offers significant potential for enhancing inclusivity and personalized learning, yet its implementation is often hindered by infrastructural limitations, lack of training, and the absence of localized, customizable tools. Using a qualitative thematic analysis approach, the study employed open-ended digital questionnaires supported by AI-assisted tools (Microsoft Word Macro and ChatGPT) to identify five major themes: enhanced teaching and learning practices, increased student engagement, need for personalized digital solutions, challenges in professional preparation, and the importance of thoughtful, balanced implementation. The findings are interpreted through the lens of Rogers’ Diffusion of Innovation Theory, highlighting how adoption dynamics are shaped by contextual challenges within Malaysia’s Digital Education Policy (2021–2030). Despite barriers, the study underscores that when technology is implemented thoughtfully and supported by adequate training and resources, it can significantly empower special education practices. The study also demonstrates the methodological innovation of integrating generative AI into qualitative analysis, contributing both theoretically and practically to the field of inclusive educational technology. The implications point to the urgent need for policy intervention, capacity-building efforts, and the development of culturally responsive digital tools to foster equitable digital transformation in special education.